THE EFFECTIVENESS OF ANAGRAM TECHNIQUE IN BUILDING VOCABULARY MASTERY - Adebya Afrilia Santika; Tri Kurniawati; Elly Syahadati (IKIP PGRI Pontianak, 2024)
AbstractThis study has two primary objectives: firstly, to assess the efficacy of the Anagram Technique in enhancing vocabulary mastery, and secondly, to establish its significance in vocabulary development for eighth-grade students at SMPN 5 Sungai Kunyit. applying a quantitative approach along with the pre-experimental design, specifically a one-group pretest-posttest design, the research involved 32 eighth-grade students, comprising 18 males and 14 females from SMPN 5 Sungai Kunyit. Data collection utilized essay tests for both pre-test and post-test assessments. The gathered data underwent analysis using descriptive statistics in SPSS version 16.0. The researcher implemented data distribution, performed a paired sample t-test for hypothesis testing, and included Cohen's effect size to evaluate the Anagram Technique's impact on vocabulary mastery.The research findings indicated the effectiveness of the Anagram Technique, as demonstrated by significant mean score differences before and after treatment (64.63 and 88.94, respectively). The lower standard deviation of the pre-test (8.36) compared to the post-test (6.72) suggested successful treatment implementation. This success was further supported by the paired sample t-test in SPSS 16.0, revealing a notable result (Sig. 0.000) at an alpha level of 0.05. Consequently, the rejection of the null hypothesis (Ho) and acceptance of the alternative hypothesis (Ha) occurred since the significance value (Sig) was below ?. Furthermore, the calculated effect size using Cohen's method (1.61) emphasized a substantial impact of the Anagram Technique on enhancing vocabulary mastery. In summary, the analysis results collectively affirmed that the Anagram Technique was an effective pedagogical approach for cultivating vocabulary proficiency among eighth-grade students at SMPN 5 Sungai Kunyit.